ANALYSIS OF THE PHYSIOLOGICAL EFFECTS THAT MILITARY FIREFIGHTERS ARE SUBJECT TO IN FIRE OPERATIONS IN CONFINED ENVIRONMENTS (REMUNOM, 2026)
Firefighting operations in confined environments impose high physiological demands on military firefighters, constituting a significant risk to physical integrity. This study analyzed the physiological effects on 121 military firefighters during controlled exposure in a Fire Development Simulator (SDI). Pre- and post-exposure parameters were evaluated: blood pressure, heart rate, oxygen saturation, compressed air consumption, and fluid loss, using Pearson correlation analysis. Results revealed strong positive correlation (r = 0.82; p < 0.001) between systolic and diastolic blood pressure variations; moderate to strong correlation (r = 0.67; p < 0.01) between heart rate and air consumption; and strong negative correlation (r = -0.78; p < 0.001) between oxygen saturation and air consumption. Average fluid loss was -1.00 kg (± 0.40 kg) in younger quartiles, with lower deficit (-0.86 kg) in the oldest quartile. Compressed air consumption emerges as a sensitive marker of physiological load, surpassing isolated variables, recommending the implementation of individualized hydration protocols and air consumption monitoring as preventive operational strategies.